Determination of optimum concentration of lime slurry for soil stabilisation - 267940 Muhammad Sofian Abdullah (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2006